ICD-11 posttraumatic stress disorder and complex PTSD: prevalence, predictors, and construct validity in Swiss older adults - Myriam V. Thoma; Enya Redican; Nathanael Adank; Valerie B. Schneemann; Mark Shevlin; Andreas Maercker; Shauna L. Rohner (European Journal of Psychotraumatology)
Background: This study assessed the prevalence rates, construct validity, predictors, and psychosocial factors linked to ICD-11 posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD), as assessed by the International Trauma Questionnaire (ITQ) in a German-speaking sample of Swiss older adults.Method: Participants were N = 1526 older adults aged 65+ (Mage = 72.34; SD = 6.20 years; age range = 65–95; female = 72.0%). Confirmatory factor analysis (CFA) tested alternative models of the latent structure of the ITQ. Risk factors and psychological outcomes associated with the ITQ subscales were also examined.Results: From the total sample, 86.2% had experienced at least one potentially traumatic event (PTE), with a median of three PTEs per person. Probable PTSD and CPTSD prevalence was 0.4% and 2.4%, respectively. CFA results indicated that a two-factor second-order model best captured the latent structure of the ITQ. Female gender and specific traumas, such as physical and sexual assault, were uniquely associated with PTSD. Fewer, non-specific factors were linked to disturbances in self-organization (DSO; encompassing affective dysregulation, a negative self-view, and difficulties in relationships). The PTSD and CPTSD factors were significantly associated with loneliness, anxiety, depression, and well-being.Conclusions: Results found that despite high trauma exposure among Swiss older adults, the prevalence of ICD-11 PTSD and CPTSD was low, with no significant gender differences. A two-factor second-order model provided the best fit for the ITQ. These findings indicate significant trauma exposure in Swiss older adults and the need for targeted interventions that address the trauma-specific and associated psychosocial challenges (i.e. loneliness, anxiety, depression, well-being) facing older adults.